Emotion recognition from facial expression of autism spectrum disordered children using image processing and machine learning algorithms - Tasnim, Nishat; Khwaja, Atiya; Rashid, Humayra (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.